If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -8) + 9 = 3(4 + -1m) + -4 Reorder the terms: 2(-8 + m) + 9 = 3(4 + -1m) + -4 (-8 * 2 + m * 2) + 9 = 3(4 + -1m) + -4 (-16 + 2m) + 9 = 3(4 + -1m) + -4 Reorder the terms: -16 + 9 + 2m = 3(4 + -1m) + -4 Combine like terms: -16 + 9 = -7 -7 + 2m = 3(4 + -1m) + -4 -7 + 2m = (4 * 3 + -1m * 3) + -4 -7 + 2m = (12 + -3m) + -4 Reorder the terms: -7 + 2m = 12 + -4 + -3m Combine like terms: 12 + -4 = 8 -7 + 2m = 8 + -3m Solving -7 + 2m = 8 + -3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3m' to each side of the equation. -7 + 2m + 3m = 8 + -3m + 3m Combine like terms: 2m + 3m = 5m -7 + 5m = 8 + -3m + 3m Combine like terms: -3m + 3m = 0 -7 + 5m = 8 + 0 -7 + 5m = 8 Add '7' to each side of the equation. -7 + 7 + 5m = 8 + 7 Combine like terms: -7 + 7 = 0 0 + 5m = 8 + 7 5m = 8 + 7 Combine like terms: 8 + 7 = 15 5m = 15 Divide each side by '5'. m = 3 Simplifying m = 3
| f(2c)=3(2c^2)+6(2c) | | -7.8=-1.4x+2 | | 6+4=120 | | -4p-5.2=11.1 | | 4x-13x-19=-73 | | f(x)=-7x^2+5x+7 | | 4x-45=3 | | f-12.3=-73.8 | | 4x-9+2x-1=14 | | -6m-6=24 | | 3x^2-36x-10=o | | 5x-6z=-17 | | 13x+8y=123 | | y-2=.75x-6 | | 6x+5+7x-3=28 | | 15+4n=9n | | -8x-22=23-5x | | 19x+1=x+37 | | -3(2x-6)=12 | | A^2-12a-13=0 | | 9(3)-(-6)+7= | | 2x-12=2+x | | 64c^2=25 | | 2(7+x)=-36 | | b/5+1/3=17 | | 11x=16500 | | (7+x)=-36 | | 5(v-7)=-45 | | y-13=-.8x-(-5) | | 0.6666x+1=x-4 | | -6t+t^2=0 | | V=Vlw |